Schimmelpenning syndrome - Resende, C; Araújo, C; Vieira, AP; Ventura, F; Brito, C (My University, 2013)
Schimmelpenning syndrome (SS) includes an organoid nevus that follows the lines of Blaschko and defects of brain, eyes, bones, or other systems. We report a case of a 3-month old female infant, who presented with several thin plaques, with irregular borders, yellowish color, which had a verrucous appearance, following the lines of Blaschko, mainly occupying the left side of posterior trunk, the left face, the right side of the anterior trunk, and the right upper limb. These plaques had been present since birth. In addition, she had a flat salmon to yellow nevus on the left parietal and temporal region of the scalp, with a bald patch. She was diagnosed after birth with an interauricular communication. The skin biopsy from the lesion of the right arm revealed an epidermal nevus that occupied the epidermis completely. Routine and other complementary laboratory blood tests, including platelet count, thyroid function tests, 25-hydroxy-vitamin D, parathyroid hormone, and plasma and urinary levels of calcium and phosphorus were negative. Cerebral magnetic resonance and renal ultrasound were normal. The diagnosis of SS was established. She is being followed in the clinics of Dermatology, Cardiology, Pediatrics, and Pediatric Neurology. We report this case to point out the importance of investigating patients with epidermal nevus to identify associated conditions.
Keywords: Nevo; Doenças da Pele